Miasto jako perpetuum mobile. Berlin. Symfonia wielkiego miasta (1927) Waltra Ruttmanna - Hendrykowska, Małgorzata (Wydawnictwo Naukowe UAM w Poznaniu; Wydawnictwo PWSFTViT w Łodzi, 2013)
The atmosphere of a big city, as well as registering the motion of the city as a symbol of modern industrial civilization, fascinated the first directors of photography at the turn of the 20th century. Some years later, the subject of the metropolis was developed by avant-garde artists. Among early cinematic images of the city, the foremost place is held by Walter Ruttmann’s 1927 film Berlin: Symphony of a Metropolis. It was the first multifaceted and comprehensive documentary picture of the city. The city is shown without any anecdote or story, without an individual hero, distinct from theatre or literature. Ruttmann shows the diversity, complexity and co-dependence of the urban organism, which becomes something of a machine in perpetual motion. Ruttmann’s film unveils the uniformity of big-city life, the unification of the imagination, expectations, needs and dreams. The world of “Berlin” is created mainly by editing. Motion – the result of artistic endeavours, together with the rhythmic order of the images, determine the artistic vision of the film as a whole. Ruttmann’s rhythmic interpretation aims at breaking the boundaries between art and non-artistic reality.

Wielkomiejska atmosfera, rejestracja pełnego ruchu miasta – symbolu nowoczesnej cywilizacji przemysłowej fascynowała już pierwszych operatorów filmowych na przełomie XIX i XX wieku. Po latach, wielkomiejskie tematy rozwinęli twórcy z kręgu szeroko rozumianej awangardy. Wśród filmowych obrazów miasta szczególne miejsce zajmuje, zrealizowany w 1927 roku, film Waltera Ruttmanna Berlin, die Sinfonie der Grosstadt. To pierwszy tak wielostronny, wieloaspektowy filmowy obraz miasta o charakterze dokumentalnym. Miasto pokazane zostaje bez anegdoty, bez historii, bez jednostkowego bohatera, odcinając się od teatru i literatury. Ruttmann pokazuje różnorodność, wielopiętrowość i współzależność organizmu miejskiego, który staje się swoistą samonapędzającą się maszyną, rodzajem perpetuum mobile. Film Ruttmanna odsłania standaryzację wielkomiejskiego życia, unifikację wyobraźni, oczekiwań, potrzeb i marzeń. Świat „Berlina” w filmie Ruttmanna kreowany jest głównie przez montaż. Ruch kreowany jako rezultat zabiegów artystycznych, uporządkowanie rytmiczne obrazu decydują o wizji artystycznej całości. Filmowa interpretacja Ruttmanna zmierza do przełamania granic oddzielających sztukę od rzeczywistości pozaartystycznej.
The City in Perpetual Motion. Berlin: Symphony of a Metropolis (1927) by Walter Ruttman
Keywords: Walter Ruttmann; Berlin: Symphony of a Metropolis; documentary film; avant-garde; urban organism; editing; rhythm; Dynamics; creation of movement; point of view of the camera; uniformity; unification; reception; film dokumentalny; awangarda; organizm miejski; montaż; rytm; dynamika; kreacja ruchu; punkt widzenia kawery; standaryzacja; unifikacja; recepcja